Are low potassium diets increasing the risk for hypokalemia induced rhabdomyolysis - Eldridge, Amy; Duriancik, David (Progress in Nutrition, 2019)
Rhabdomyolysis is a serious medical condition caused from degraded skeletal tissue leading to the release of intracellular protein and severe electrolyte imbalance. There are different causes of rhabdomyolysis that include alcohol and substance abuse, anorexia, gastrointestinal complications, medication induced, high intake of caffeine, muscular trauma, and intense exercise. The objectives are to identify diet history, current treatments used for hypokalemia, and recommendations for future prevention of hypokalemia. With rhabdomyolysis being diagnosed once a patient has been hospitalized, it is vital for clinicians to consider other circumstances that may increase the risk for hypokalemia induced rhabdomyolysis.